Barriers and Facilitators in Access to Diabetes, Hypertension, and Dyslipidemia Medicines: A Scoping Review - Carla Castillo-Laborde; Macarena Hirmas-Adauy; Isabel Matute; Anita Jasmen; Oscar Urrejola; Xaviera Molina; Camila Awad; Catalina Frey-Moreno; Sofia Pumarino-Lira; Fernando Descalzi-Rojas; Tomás José Ruiz; Barbara Plass (Frontiers Media S.A., 2022)
Objective: Identify barriers and facilitators in access to medicines for diabetes, hypertension, and dyslipidemia, considering patient, health provider, and health system perspectives.Methods: Scoping review based on Joanna Briggs methodology. The search considered PubMed, Cochrane Library, CINAHL, Academic Search Ultimate, Web of Science, SciELO Citation Index, and grey literature. Two researchers conducted screening and eligibility phases. Data were thematically analyzed.Results: The review included 219 documents. Diabetes was the most studied condition; most of the evidence comes from patients and the United States. Affordability and availability of medicines were the most reported dimension and specific barrier respectively, both cross-cutting concerns. Among high- and middle-income countries, identified barriers were cost of medicines, accompaniment by professionals, long distances to facilities, and cultural aspects; cost of transportation emerges in low-income settings. Facilitators reported were financial accessibility, trained health workers, medicines closer to communities, and patients' education.Conclusion: Barriers and facilitators are determined by socioeconomic and cultural conditions, highlighting the role of health systems in regulatory and policy context (assuring financial coverage and free medicines); providers' role bringing medicines closer; and patients' health education and disease management.